Literature Review : Peran dan Strategi Komunikasi Efektif dalam Manajemen Perubahan Organisasi - Wadiv Vatul Khovivah; Mareta Rofiko; Danial Atiq Ma’shum; Santi Nur Holisa; Qinta Istiqlalia Hidaya; Nikmatul Wafiah; Mu’alimin Mu’alimin (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
Effective communication serves as a fundamental pillar for organizational success, particularly in navigating dynamic change. This study aims to explore the role of effective communication within organizations and identify applicable strategies to address common communication challenges in complex and evolving work environments. The research employs a literature review method, selecting 15 relevant articles and conducting an in-depth analysis of the 5 most credible ones. The findings indicate that effective communication enhances teamwork, clarifies organizational goals, fosters trust, and improves overall productivity. However, various challenges such as misunderstandings, cultural differences, technological limitations, and resistance to change can hinder communication effectiveness. To overcome these barriers, organizations must implement strategic approaches, including fostering open and transparent communication, utilizing adaptive communication technologies, providing communication skills training, managing cultural diversity, and conducting regular evaluations of communication processes. These strategies contribute to creating a communicative, inclusive, and high-performing organizational environment.